Candida albicans mucin Msb2 is a broad-range protectant against antimicrobial peptides - Swidergall, Marc; Ernst, Andreas M.; Ernst, Joachim F. (Antimicrobial agents and chemotherapy, 2013)
The human fungal pathogen Candida albicans releases a large glycofragment of the Msb2 surface protein (Msb2*) into the growth environment, which protects against the action of human antimicrobial peptides (AMPs) LL-37 and histatin-5. Quantitation of Msb2*/LL-37 interactions by microscale thermophoresis revealed high-affinity binding (dissociation constant [KD] = 73 nM), which was lost or greatly diminished by lack of O-glycosylation or by Msb2* denaturation. Msb2* also interacted with human α- and β-defensins and protected C. albicans against these AMPs. In addition, the lipopeptide antibiotic daptomycin was bound and inactivated by Msb2*, which prevented the killing of bacterial pathogens Staphylococcus aureus, Enterococcus faecalis, and Corynebacterium pseudodiphtheriticum. In coculturings or mixed biofilms of S. aureus with C. albicans wild-type but not msb2 mutant strains, the protective effects of Msb2* on the bactericidal action of daptomycin were demonstrated. These results suggest that tight binding of shed Msb2* to AMPs that occurs during bacterial coinfections with C. albicans compromises antibacterial therapy by inactivating a relevant reserve antibiotic.
Gesehen am 27.01.2022